(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2021)
Defence were devoting a big deal of attention towards what was going on in Italy, and what the elections’ outlook might bring about. Among the many issues discussed in numerous reports concerning the Italian situation, assessments diverged about the repercussions of the Communists’ share of power on the Italian democratic system. Relying upon archival sources available at the National Archives in Kew (London), the essay explores the debate that took place and the dangers then envisaged for the Italian democracy.